Estaquia em Anonas - Scaloppi Junior, Erivaldo José; Martins, Antonio Baldo Geraldo [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
Annonaceae is an important family of plants that constitutes the Brazilian flora. Anona species produce fruits for fresh consumption, medicinal use and other purposes. The aim of this study is to present information of literature about vegetative propagation by cutting of some Annonaceae species with potential for consumption and as rootstock. As conclusion, the literature presents a range of rooting results, even about the same species. The rooting success depends on the species, variety, stock plant, season, plant growth regulators, rooting environment and juvenility. Some species present rooting potential, but there are lack of literature about plant management and orchard installation. The use of plant growth regulators improves the rooting of the most species with potential to propagate by cuttings.

Annonaceae é uma importante família de plantas constituintes da flora nacional com espécies produtoras de frutos para consumo in natura, medicinal e para diversos fins. O objetivo do artigo é apresentar informações disponíveis na literatura sobre a propagação vegetativa por estaquia de algumas espécies de Annonaceae com potencial para consumo in natura e como porta-enxerto, principalmente. Conclui-se que a literatura apresenta resultados de enraizamento variados, mesmo dentro de espécie. O sucesso do enraizamento de estacas é dependente de fatores como espécie, variedade, planta-matriz, época do ano, reguladores vegetais, ambiente de enraizamento e juvenilidade. Algumas espécies de Annonaceae apresentam potencial para a propagação por estacas, porém a literatura é escassa de trabalhos referentes à formação de muda e condução de plantio. A utilização de reguladores vegetais exógenos favorece o enraizamento na maioria das espécies com potencial para a propagação por estacas.
Anonas cutting
Keywords: Annonaceae; Annona spp.; Rollinia spp.; Vegetative propagation; asexual reproduction; Annonaceae; Annona spp.; Rollinia spp.; Propagação vegetativa; multiplicação assexuada